Method for preparing easily dispersible hydrocolloid compositions
A two-step agglomeration process using xanthan gum, carboxymethylcellulose, and maltodextrin with calcium salts enhances hydrocolloid dispersibility, addressing clumping issues and improving dysphagia management by ensuring rapid hydration and effective thickening.
Patent Information
- Application Number
- JP2022501603
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-22
- Filing Date
- 2020-03-19
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2040-03-19
AI Technical Summary
Existing hydrocolloid-based thickeners for managing dysphagia have poor dispersibility in water, leading to clumping and slow hydration, which complicates their use in modifying food and liquid rheology for safer swallowing.
A method involving a two-step agglomeration process using xanthan gum, carboxymethylcellulose, and maltodextrin, combined with calcium salts and maltodextrin solutions, to create easily dispersible hydrocolloid compositions that can be stirred with a spoon without vigorous mixing.
The method produces hydrocolloid compositions that disperse rapidly and uniformly in water, providing effective thickening for improved swallowability and reduced aspiration risk, suitable for managing dysphagia without forming clumps.
Smart Images

Figure 0007599474000001 
Figure 0007599474000002
Abstract
Description
REFERENCE TO RELATED APPLICATIONS
[0001] This patent application claims priority to Japanese Patent Application No. 2019-055510, filed on March 22, 2019, the entire disclosure of which is incorporated herein by reference. [Technical field]
[0002] The present invention relates to a method for preparing a readily dispersible hydrocolloid composition and the use of said composition prepared by said method in the management of dysphagia. [Background technology]
[0003] Dysphagia is a condition resulting from a disorder in the swallowing mechanism that may result in the impairment of the safety, efficiency or quality of eating and drinking.Dysphagia can be caused by a number of disorders, including neurological disorders such as stroke, traumatic brain injury, Huntington's disease, multiple sclerosis, Parkinson's disease and cerebral palsy.Many of these conditions are associated with the elderly and continuing demographic changes, making dysphagia a problem of increasing severity.
[0004] To address dysphagia, it is an established clinical practice to use foods and liquids with modified texture or rheology. This practice has been based on the hypothesis that modifying the rheology of common foods and liquids makes them easier and safer to swallow. It is generally accepted that thin liquids such as water, tea, coffee, squash, and juices flow quickly through the oral cavity during the swallowing process and may induce aspiration. Aspiration is the ingress of food or liquid into the airways and is often manifested as coughing or choking during swallowing. This leads to resistance to eating or drinking with the subsequent risk of malnutrition or dehydration. If unmanaged over a long period of time, aspiration can lead to respiratory complications such as chronic obstructive pulmonary disease or aspiration pneumonia. A common practice is to increase the liquid viscosity to reduce the risk.
[0005] One class of thickeners used in products for managing dysphagia are hydrocolloids. Hydrocolloids are often provided by manufacturers in the form of dry granules, which can be difficult to disperse in water or other liquids as they tend to clump during hydration. The physicochemical basis for hydrocolloids clumping during hydration and dispersion is the surface-to-surface cross-linking and / or gelation of polymer molecules at the surface of the hydrocolloid granules. At this stage, the hydrated polymer molecules at the granule surface are fully or partially released from the surface. This results in a high concentration of hydrated polymer at or near the granule surface. When granules are added to liquid / water, there are thousands of particles in a small volume, but each of them is surrounded by a liquid "cloud" with a high local polymer concentration that can potentially cross-link to form gels between the granules, which will then become sticky and clump together. The formation of clumps slows down the entire dissolution process as a result of limited liquid access to the interior of the clump. Summary of the Invention [Problem to be solved by the invention]
[0006] There is a need to develop hydrocolloid-based thickener compositions for managing dysphagia with improved dispersibility in water or aqueous solutions that allow for rapid hydration and solubilization. [Means for solving the problem]
[0007] In the course of developing a hydrocolloid-based product with improved rheological properties for managing dysphagia, the inventors have developed a method of combining xanthan gum and carboxymethylcellulose in a composition that does not form lumps when dispersed in water and does not require vigorous agitation to disperse, but can be stirred with a spoon by the end user (e.g., the dysphagic patient or caregiver).
[0008] Accordingly, the present invention provides a method for preparing a readily dispersible hydrocolloid composition, comprising the steps of: (a) providing a dry blend of xanthan gum, carboxymethyl cellulose and maltodextrin in powder form; (b) contacting the dry blend of step (a) with a solution of a calcium salt to provide a first aggregate: (c) contacting the first agglomerates of step (b) with a solution of maltodextrin to provide second agglomerates; and (d) recovering the second aggregate.
[0009] In another aspect, the invention relates to the readily dispersible hydrocolloid compositions prepared by the method.
[0010] In yet another aspect, the present invention relates to a readily dispersible hydrocolloid composition for use in the management of dysphagia. [Brief description of the drawings]
[0011] [Figure 1] Schematic diagrams showing powder granules during hydration, showing (A) good dispersion and rapid dissolution, (B) poor dispersion and slow dissolution, and (C) very poor dispersion and extremely slow dissolution. Easy dispersibility is shown as rapid hydration and dissolution of separate granules, while poor or very poor dispersibility is shown as slow hydration of the granules. [Diagram 2] FIG. 1 shows a schematic diagram of the agglomeration of hydrocolloid granules (shown as irregular shapes) and a binder component (shown as round shapes) in a simplified fluidized bed process in which poorly dispersed hydrocolloid granules are sprayed with a solution of a binder component, thereby binding the hydrocolloid granules into larger agglomerated particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] definition In the context of the present invention, the term "hydrocolloid" is intended to denote a hydrophilic substance capable of forming a colloidal dispersion of fine particles in a liquid, in particular in water. The colloidal particles bind water by hydrogen bonds. Examples of hydrocolloids are biopolymers, such as alginates, carrageenans, pectins, cellulose derivatives such as carboxymethylcellulose, xanthan gum, succinoglycan, gellan, guar gum, locust bean gum and starch. A preferred hydrocolloid is the cellulose derivative, xanthan gum. In the context of the present invention, "hydrocolloid" is used collectively to mean xanthan gum and carboxymethylcellulose. A "hydrocolloid composition" is a composition comprising particles of hydrocolloids.
[0013] The term "easily dispersible" or "easily dispersible" is intended to indicate the ability of aggregated particles of a hydrocolloid composition to be immersed and flow as free single particles in water or an aqueous solution without clumping or agglomeration, immediately followed by complete hydration and eventual dissolution of the particles. See FIG. 1A. Preferably, dispersion of the particles can be performed without application of high shear forces, e.g., by stirring with a spoon, and clump-free dispersion is performed within less than 1 minute of stirring.
[0014] The term "aggregate" is intended to denote a particle composed of multiple granules of hydrocolloid and one or more readily dispersible or water-soluble components that act as binders to hold the hydrocolloid granules together. See Figure 2. Upon hydration, the readily dispersible components dissolve and the hydrocolloid granules separate, primarily as a result of turbulence and liquid dispersion within the liquid microenvironment and within the aggregates.
[0015] The term "xanthan gum" is intended to mean the polysaccharide produced by the luminescence of the microorganism Xanthomonas campestris. Examples of commercially available xanthan gums are GRINSTED Xanthan Clear 80 (available from DuPont), GRINSTED Xanthan MAS-SH (available from DuPont), SAN ACE (available from San-Ei Gen FFI), KELTROL (available from CP Kelco) and ECHO GUM (available from DSP Gokyo Food & Chemical).
[0016] The term "carboxymethylcellulose" (abbreviated herein as "CMC") is intended to mean a cellulose derivative prepared by replacing hydrogen in some of the hydroxyl groups on the anhydroglucose units of a cellulose polymer with a carboxymethyl group (-CH2-COOH). Commercially available examples of carboxymethylcellulose include GRINSTED BEV130 (available from DuPont), GRINSTED BEV150 (available from DuPont), GRINSTED BEV 350 (available from DuPont) and WALOCEL C (available from Dow Chemical).
[0017] Embodiment Surprisingly, it has been found that a two-stage aggregation process can provide an easily dispersible hydrocolloid composition in the form of a powder.
[0018] In step (a) of the process, the granular xanthan gum and CMC are dry blended with maltodextrin powder. Maltodextrin is a water-soluble sugar that is easily dispersible in water, providing dilution and physical separation of the xanthan gum and CMC granules. The concentration of maltodextrin in the dry blend of step (a) is conveniently in the range of 40-90% by dry weight, preferably 50-80% by dry weight.
[0019] The objective of the method of the present invention is to provide an easily dispersible hydrocolloid composition with a rheology suitable for the management of dysphagia, which provides thickness to foods and beverages to improve their swallowability. Efforts have been made to thicken smooth liquids for people with dysphagia to prevent aspiration. The degree of such thickening varies depending on the severity of the dysphagia of the individual patient, requiring professionals such as physicians, speech therapists (STs), nutritionists, etc. to adjust the thickening according to the behavior of the individual patient. The hydrated composition must exhibit the following characteristics: The hydrated composition must exhibit non-Newtonian flow behavior. The hydrated composition must exhibit a fairly high viscosity at low shear rates, as this will increase the residence time on the tongue. The hydrated composition is allowed to flow within the pharyngeal wall for 50 to 100 seconds. -1 Although the shear rate is lower, the fluid must still exhibit a viscosity sufficient to reduce the risk of aspiration as it flows around the epiglottis.
[0020] In general, it has been found that the desired viscosity can be achieved when the ratio of xanthan gum to carboxymethylcellulose in step (a) is from 90:10 to 30:70, preferably from 85:15 to 40:60, and more preferably from 80:20 to 50:50.
[0021] The total concentration of the two hydrocolloids in the dry blend of step (a) is conveniently in the range of 10-60% by dry weight, preferably 20-50% by dry weight, of the dry blend.
[0022] Two-stage aggregation is carried out in steps (b) and (c) of the method. Aggregation is a process in which an easily dispersible component is added to hydrocolloid granules and the particle size is increased at the same time, which typically improves dispersibility and reduces clumping. The enlarged particles are composed of multiple granules of two hydrocolloids physically bound together with an easily dispersible binder component (e.g., maltodextrin). Upon hydration and dissolution, the binder dissolves and separates the hydrocolloid granules, mainly as a result of turbulence and liquid dispersion within the liquid microenvironment and within the aggregates. For those hydrocolloid compositions prepared by the two-stage aggregation process, superior dispersibility has been found in contrast to compositions prepared in a process in which solutions of calcium salt and maltodextrin are applied simultaneously. See Example 1 compared to Example 4.
[0023] In the present process, the agglomeration can be carried out by spraying an aqueous solution of the easily dispersible components onto a dry blend of hydrocolloid and maltodextrin in a fluidized bed (particularly a moving fluidized bed). The spray rate must be balanced with the drying rate and shear in the equipment used, and together these parameters govern the size growth of the aggregates. It will be readily apparent to one skilled in the art that each of the parameters of the present process can be adjusted to suit the equipment used in the process. In step (b) of the present process, the aqueous solution contains a calcium salt. It is currently believed that the presence of calcium retards the hydration, and consequently the stickiness, of the hydrocolloid, thus allowing the hydrocolloid granules to become sticky and disperse in water before being left to form lumps. Examples of suitable calcium salts are calcium lactate, calcium propionate, calcium citrate and calcium chloride. It is preferred to include calcium salts in concentrations close to the solubility limit of the particular calcium salt in question, as this allows for reduced spray times. The currently preferred calcium salt is calcium lactate, as it produces the desired dispersibility of the hydrocolloid composition. The concentration of calcium lactate in the aqueous solution of step (b) may be, for example, up to 10%, preferably up to 9.1%, more preferably 5% to 9.1% for calcium lactate anhydrous, and for example, up to 15%, preferably up to 12.8%, more preferably 5% to 12.8% for calcium lactate, 5H2O. Another calcium salt, calcium propionate, may be included in the aqueous solution of step (b) at a concentration of up to 15%. The concentration of calcium salt in the final composition is typically in the range of 1 to 10% of the dry weight of the composition, preferably in the range of 1 to 5% of the dry weight of the composition.
[0024] In step (c) of the method, the liquid solution sprayed onto the agglomerated particles prepared in step (b) preferably contains maltodextrin, more preferably at a concentration close to the solubility limit of the particular grade of maltodextrin. Maltodextrin is available in various grades expressed as dextrose equivalents (DE) ranging from 3 to 20. The higher the DE value, the shorter the glucose chains and the higher the solubility. For example, if the maltodextrin is a maltodextrin with a DE value of 6, it may be included in the aqueous solution of step (c) at a concentration of 33.3%. The concentration of maltodextrin added to the composition in step (c) may be in the range of 2 to 20% of the dry weight of the composition. Subsequent coagulation with a maltodextrin solution is required to build and strengthen the aggregates as the calcium salt is a poor binder, resulting in small, weak aggregates when used alone, whereas the maltodextrin is believed to provide the cohesiveness resulting in stronger and larger aggregates formed in the present process.
[0025] The agglomerated particles can be recovered by releasing them from the fluidized bed. The particles typically have 20-80% of the particles having a particle size of 200 μm or greater, and at least 90% of the particles having a particle size greater than 50 μm. Particle size can be determined on a Malvern Mastersizer 3000 using the Mie scattering model.
[0026] The resulting hydrocolloid composition is easily dispersible in water or aqueous solutions. Dispersibility can be determined by placing a glass beaker (Φ 4 cm, equipped with a 3 cm stirring magnet) containing 100 mL of model tap water (deionized water containing 0.025% NaCl by weight) on a magnetic stirrer. Then, 2 g of the agglomerated particles are poured into the glass beaker and the magnetic stirrer is switched on after 2 seconds. Stirring at 600 rpm is maintained for 10 seconds, after which the magnetic stirrer is switched off. The degree of agglomeration is assessed visually. The samples are ranked from 1 to 5, where 1 means the appearance of very large, poorly hydrated agglomerates, 2 means the appearance of large and medium-sized agglomerates, both well and poorly hydrated, 3 means the appearance of medium and small agglomerates, both well and poorly hydrated, 4 means the appearance of a few small, well-hydrated agglomerates that dissolve within a few minutes, and 5 means the absence of agglomerates. A dispersity of 3 is considered acceptable, however a dispersity of 4 or 5 is preferred.
[0027] The hydrocolloid composition was determined to have a 50% aggregated particle size distribution when a sample of the aggregated particles in water was determined to have a 2% aggregated particle size distribution by weight. -1 The viscosity range is found to be effective for the management of dysphagia. The viscosity can be determined as follows: Samples are prepared by slowly adding the agglomerated particles to tap water in a beaker. The sample is stirred at 500 rpm for 30 minutes, then removed from the stirrer, a magnetic bar is added, and the sample is stirred overnight. The samples were left unstirred for at least 5 min and then run in an MCR501 rheometer (Anton Paar) to measure the flow curve (0.001 s at 20 °C). -1 ~1,000s -1 ) is measured. The agglomerated particles preferably have a bulk density of 20-50 g / 100 mL as measured by gravimeter in a 100 mL glass cylinder (Φ, approximately 4 cm).
[0028] For use in the management of dysphagia, a 1-3% by weight hydrocolloid composition comprising 20-50% by weight hydrocolloid and 50-80% by weight maltodextrin can be suitably dispersed in cold tap water and immediately stirred with a spoon to provide the desired viscosity. The hydrocolloid composition of the present invention can also be added to hot beverages such as tea, coffee, broth, etc. in suitable concentrations to provide the desired viscosity.
[0029] According to another aspect of the invention there is provided the use of a readily dispersible hydrocolloid composition in the manufacture of a composition for use in the management of dysphagia.
[0030] According to another aspect of the present invention there is provided the use of a readily dispersible hydrocolloid composition in the manufacture of a composition for providing viscosity to a food or beverage to improve the swallowability of the food or beverage.
[0031] According to another aspect of the present invention, there is provided a readily dispersible hydrocolloid composition for providing viscosity to food or beverages to improve the swallowability of the food or beverages.
[0032] According to another aspect of the present invention there is provided the use of a readily dispersible hydrocolloid composition for use in the management of dysphagia. According to one preferred embodiment of the present invention the use of the present invention is a non-therapeutic use.
[0033] According to another aspect of the present invention, there is provided the use of a readily dispersible hydrocolloid composition for providing viscosity to a food or beverage to improve the swallowability of the food or beverage.
[0034] According to another aspect of the present invention, there is provided a method for providing viscosity to a food or beverage to improve the swallowability of the food or beverage, comprising adding a readily dispersible hydrocolloid composition to the food or beverage.
[0035] According to another aspect of the present invention, there is provided a method for managing dysphagia, comprising feeding a person with dysphagia a food or drink to which has been added a readily dispersible hydrocolloid composition, wherein, according to another preferred aspect of the present invention, said method is exclusive of medical treatment of humans.
[0036] All of the above use, composition and method aspects may be carried out in accordance with the description of the readily dispersible hydrocolloid compositions of the present invention and their preparation methods.
[0037] The present invention is further described in the following examples, which in no way limit the scope of the invention as claimed. EXAMPLES
[0038] Example 1: Two-stage flocculation process Prototypes were prepared in a pilot-scale fluidized bed (Aeromatic Fielder MP1) equipped with a top spray at a batch size of 1,000 g using a two-fluid nozzle (Schlick 970-S4) with a 1.0 mm liquid pipe.
[0039] 300 g of hydrocolloids (Xanthan gum MAS-SH and CMC BEV 150, 50:50, both available from DuPont) were dry blended with 572 g of maltodextrin DE6 (Glucidex 6 IT, available from Roquette). Binder solutions were prepared by mixing calcium lactate or maltodextrin, respectively, in pre-boiled deionized water at 80° C., after which the solution was maintained at 65° C. throughout the subsequent spraying process.
[0040] The fluidized bed was preheated with 70°C process air to an exhaust temperature of 27-32°C. The fluidized bed was then charged with a dry blend of hydrocolloid and maltodextrin. Sufficient fluidization of the product bed was achieved at 25 m 3For observations taken at 1000 g / hour (1 min), the agglomeration process was initiated by spraying 300 g of a first binder solution containing 9.1 wt% calcium lactate anhydrous or 12.8 wt% calcium lactate, 5H2O in water onto the dry blend. After the first binder solution was sprayed onto the dry blend of hydrocolloid and maltodextrin to form the first agglomerates (approximately 30-45 min), a second binder solution (100 g maltodextrin dissolved in 200 g water) was sprayed onto the first agglomerates for 30-45 min to form the second agglomerates.
[0041] In both agglomeration steps, the atomizing air had a pressure of 1.8 bar and a temperature of 45° C. The fluidizing air temperature was constant at 70° C. throughout the entire agglomeration process. The flow rate of the fluidizing process air was 25 m 3 / hour~50m 3 / hour, and the remaining time of the process is increased to 50m 3 / hr.
[0042] When all of the second binder solution had been added, the second aggregate was immediately drained from the fluidized bed through a sampling hole in the Φ20 mm tube using a custom-made vacuum system, while the aggregate was fluidized to avoid fine particles from the internal filter falling into the aggregate.
[0043] The resulting aggregates had a bulk density of 25 g / 100 mL and a dispersity of 4 (determined by the magnetic stirrer method described above).
[0044] Example 2: Two-stage flocculation process Agglomerates containing the hydrocolloids xanthan gum MAS-SH and CMC BEV150 and maltodextrin were prepared as described in Example 1, except the amount of aqueous solution was reduced to 150 g.
[0045] The resulting aggregates had a bulk density of 19 g / 100 mL and a dispersity of 4 (determined by the magnetic stirrer method described above).
[0046] Example 3: Two-stage flocculation process Agglomerates containing the hydrocolloids xanthan gum MAS-SH and CMC BEV150 and maltodextrin were prepared as described in Example 1, except that the first binder solution contained 15 wt. % calcium propionate in 200 g water.
[0047] The resulting aggregates had a dispersity of 4 (determined by the magnetic stirrer method described above).
[0048] Example 4 (Comparative): One-stage flocculation process Agglomerates containing the hydrocolloids xanthan gum MAS-SH and CMC BEV150 and maltodextrin were prepared as described in Example 1, except that 9.1 wt% calcium lactate anhydrous or 12.8 wt% calcium lactate, 5H2O and 50 g maltodextrin were dissolved in 300 g water and applied as a single binder solution.
[0049] The resulting aggregates had a bulk density of 23.9 g / 100 mL and a dispersity of 2 (determined by the magnetic stirrer method described above).
[0050] Example 5 (Comparative): One-stage flocculation process Agglomerates containing xanthan gum MAS-SH and CMC BEV150 blended with maltodextrin were prepared as described above, except that only one binder solution was applied, containing 100 g maltodextrin in 200 g water.
[0051] The resulting aggregates had a dispersity of 3 (determined by the magnetic stirrer method described above).
[0052] Example 6: Two-stage flocculation process 45 kg of hydrocolloids (Xanthan gum MAS-SH and CMC BEV150, 50:50) were dry blended with 85.73 kg of maltodextrin index #2AG (available from Matsutani Chemical Industry Co., Ltd.) 45 kg of a 12.8 w / w% solution of calcium lactate, 5H2O was prepared as the first binder solution, and 45 kg of a 30 w / w% solution of maltodextrin was prepared as the second binder solution.
[0053] The flocculation process was carried out under the following parameters: Inlet air temperature: 70℃ Outlet air temperature: 45~50℃ Spray rate during calcium lactate addition: 0.55-0.67 kg / min (33-40 kg / hr) Spray rate during maltodextrin addition: 0.95 kg / min (57 kg / hr)
[0054] After application of the entire calcium spray solution and then the maltodextrin solution, post drying was carried out for approximately 5 minutes.
[0055] After opening the bed for draining, the fine particle layer on top of the product bed was scraped off and a sample taken for dispersibility testing. The resulting agglomerates had a dispersibility of 5 (determined by the magnetic stirrer method described above).
[0056] Example 7: Two-stage flocculation process using different grades of CMC Prototypes were prepared in a 1,000 g batch size in a pilot-scale fluidized bed (Aeromatic Fielder MP1) equipped with a top spray using a two-fluid nozzle (Schlick 970-S4) with a 1.0 mm liquid pipe.
[0057] 400 g of a 50:50 blend of hydrocolloids (Xanthan gum MAS-SH and Carboxymethylcellulose: CMC BEV 150 available from DuPont; Blanose 7H3SF available from Ashland; Walocel CRT 20000PA available from Dow Chemical Company) was dry blended with 498 g of maltodextrin DE20. Binder solutions were prepared by mixing calcium lactate or maltodextrin, respectively, in pre-boiled deionized water at 80° C., after which the solution was maintained at 65° C. throughout the subsequent spraying process.
[0058] The fluidized bed was preheated to an exhaust temperature of 27-32°C using process air at 70°C. The bed was then charged with a dry blend of hydrocolloid and maltodextrin. Sufficient fluidization of the product bed was achieved at 25 m 3 For the observations at 1000 / hour (1 min), the agglomeration process was initiated by spraying 240 g of a first binder solution containing 9.1 wt% calcium lactate anhydrous or 12.8 wt% calcium lactate, 5H2O in water onto the dry blend. After the first binder solution was sprayed onto the hydrocolloid and maltodextrin blend to form the first agglomerates (approximately 30-45 min), a second binder solution (240 g of a 33.3% maltodextrin solution in water) was sprayed onto the first agglomerates for 30-45 min to form the second agglomerates.
[0059] In both agglomeration steps, the atomizing air had a pressure of 1.8 bar and a temperature of 45° C. The fluidizing air temperature was constant at 70° C. throughout the entire agglomeration process. The flow rate of the fluidizing process air was 25 m 3 / 50m from time 3 / hr and 50 m during the time of spraying the first binder solution. 3 To spray the second binder solution, the fluidizing air flow rate was maintained at 60 m 3 / hour.
[0060] When all of the second binder solution had been added, the second aggregate was immediately drained from the fluidized bed through a sampling hole in the Φ20 mm tube using a custom-made vacuum system while the aggregate was fluidized to avoid fine particles from the internal filter falling into the aggregate.
[0061] The resulting agglomerates containing CMC BEV150 had a bulk density of 40 g / 100 mL and a dispersity of 4 (determined by the magnetic stirrer method described above); the agglomerates containing Blanose 7H3SF had a bulk density of 50 g / 100 mL and a dispersity of 4 (determined by the magnetic stirrer method described above); and the agglomerates containing Walocel CRT20000PA had a bulk density of 44 g / 100 mL and a dispersity of 3 (determined by the magnetic stirrer method described above).
Claims
1. 1. A method for preparing a readily dispersible hydrocolloid composition comprising: (a) providing a dry blend of xanthan gum, carboxymethyl cellulose and maltodextrin in powder form; (b) contacting the dry blend of step (a) with a solution of a calcium salt to provide a first aggregate; (c) contacting the first agglomerates of step (b) with a solution of maltodextrin to provide second agglomerates; and (d) recovering the second aggregate.
2. 2. The method of claim 1, wherein the agglomeration step (b) is carried out by spraying a solution of calcium salt onto the dry blend provided in step (a) in a fluidized bed.
3. 3. The method of claim 1 or 2, wherein the agglomeration step (c) is carried out by spraying a solution of maltodextrin onto the agglomerates of step (b) in a fluidized bed.
4. 4. The method according to any one of claims 1 to 3, wherein the ratio of xanthan gum to carboxymethyl cellulose in step (a) is from 90:10 to 30:
70.
5. The method according to any one of claims 1 to 4, wherein the concentration of xanthan gum and carboxymethylcellulose in step (a) is from 10 to 60% by dry weight of the composition.
6. The method according to any one of claims 1 to 5, wherein the concentration of maltodextrin in step (a) is from 40 to 90% by dry weight of the composition.
7. The method according to any one of claims 1 to 6, wherein the concentration of the calcium salt in step (b) is 1 to 10% by dry weight of the composition.
8. The method according to any one of claims 1 to 7, wherein the calcium salt is selected from the group consisting of calcium lactate, calcium propionate, calcium citrate and calcium chloride.
9. The method according to any one of claims 1 to 8, wherein the concentration of maltodextrin in step (c) is from 2 to 20% by dry weight of the composition.
10. 10. The method of any one of claims 1 to 9, wherein 20-80% of the second agglomerates recovered in step (d) have a particle size greater than 200 μm, and at least 90% of the agglomerated particles of step (d) have a particle size greater than 50 μm.
11. A readily dispersible hydrocolloid composition prepared by the method of any one of claims 1 to 10.
12. A 2% w / w sample of the agglomerated particles in water was -1 12. The composition of claim 11, having a viscosity of 100 to 400 mPa.s at a shear rate of 100 to 400 mPa.s.
13. The composition of claim 11 or 12, wherein the agglomerated particles have a dispersibility of 3 or greater as determined by a method comprising stirring a 2% sample of the agglomerated particles in water using a magnetic stirrer at 600 rpm for 10 seconds and visually assessing the degree of clumping in the water.
14. The composition of any one of claims 11 to 13, wherein the agglomerated particles have a bulk density of 20 to 50 g / 100 mL.
15. A composition according to any one of claims 11 to 14 for use in the management of dysphagia.
Citation Information
Patent Citations
Method for granulating powder and easily dispersive / easily soluble granule composition
JP2008068194A
Thickener granule and method for producing the same
JP2011229440A
Thickening agent having dispersibility and viscosity development
JP2011244809A
